Wallenberg Sindrome: A Case Report (International Journal of Medical and Surgical Sciences, 2017)
Wallenberg's Syndrome represents 36 % of strokes in the brainstem. It is due to occlusion of the inferior cerebellar artery, affecting structures found in the cerebellum and the lateral part of the medulla oblongata. The main risk factor is atherosclerosis. The case is about a 57-year-old male patient with a history of lacunar infarcts in the cerebellum, type 2 diabetes mellitus, smoking and dyslipidemia. It begins with an intense and sudden occipital headache, without attenuating, concomitantly vertigo, hiccups, nausea, vomiting and paresthesia of lower limbs. At the physical examination, decreased peripheral pulses present Horner's syndrome, hypoesthesia, hypoesthesia in left hemiface, and contralateral hemibody, with ataxia, dysmetria and dysdiadochokinesia. MRI was performed with diffusion with diagnostic Hyperintense image of irregular morphology in the left lateral contour of the medulla oblongata, compatible with ischemic event (Wallenberg syndrome). Antithrombotic treatment and physical therapy was indicated. Patient was evaluated 2 months later showing ample improvement. It is a very specific syndrome, whose clinical manifestation depends on the anatomical region affected and abstracts the clinician from other diagnoses.
Keywords: Wallenberg syndrome; Lateral bulbar syndrome; inferior cerebellar artery